Epidemic Intelligence Threat Reporting Profile in Portugal during the COVID-19: 2 Years of Decrease in Reporting on Non-COVID-19 Threats - Vasco Ricoca Peixoto; Berta Grau-Pujol; Matilde Ourique; Renato Lourenço da Silva; Mariana Ferreira; Ana Firme; Alexis Sentís; Paula Vasconcelos (Karger Publishers, 2024)
Background: Epidemic intelligence (EI) ensures early detection, assessment, and communication of public health threats. Threat reporting defines priorities and mobilize resources for surveillance, prevention, and control. In Portugal, the Directorate-General of Health (DGS) is responsible for EI and publishes a weekly public health threat report (RONDA). Changes in threats in regular threat reports since COVID-19 have not been previously described. We analysed changes in non-COVID threat reporting in the weekly threat report. Methods: Using the DGS Emergency Operations Centre's threat reporting database, we compared threats reported in RONDAs from 2016 to 2022 in three sequential periods: P1 before COVID-19 (January 2016-March 2020), P2 during acute COVID-19 restrictions (April 2020-February 2022), and P3 in post-acute COVID-19 phase (February 2022-September 2022). We described the monthly average frequency of reports on non-COVID-19 threats in those periods considering different disease groups, geographical focus, and information sources. We estimated expected non-COVID-19 reports on threats using a forecast model fitted to the time series until March 2020 and compared observed and expected values. Results: Non-COVID-19 threats had a decrease in the monthly average frequency of reporting in period 2 (x¯1: 4.7 vs. x¯: 2.3, p < 0.001) compared to period 1. Using the forecast methods, there were 114 fewer non-COVID threats than the 162 expected (−70%) in period 2. In period 3, there were 105 more threats than expected (+256%). The ECDC and the WHO were the most frequent sources of information followed by national Public Health sources. Conclusions: During COVID-19, there was a decrease in reports on non-COVID threats in Portugal. COVID-19 possibly affected global EI, by shifting attention and resources from other threats to the pandemic. However, the number of threats that warrant follow-up and communication is increasing. Further research is necessary to inform the EI research and development agenda, to ensure that all relevant threats are detected, accessed, and communicated according to evolving EI objectives and priorities while resources and preparedness are guaranteed.